Development of Application Supports Learning on Smartphone by Augmented Reality Technology Using KWL Activity for Higher Education Institution in Thailand - Seewangkum, Dussadee (Progress in Applied Science and Technology, 2021)
Recently, there has been a proliferation of education technology practices, based on the application of active teaching and learning processes using Augmented Reality technology. The purposes of this research are: 1) to development the application supports learning on smartphone by augmented reality technology using KWL (Know-Want-Learn) activity; 2) to evaluate the effectiveness of the application supports learning AR with KWL activity; and 3) to compare students’ learning achievement between pretest and posttest of the students learning through this application. This type of research is experimental research with one group pretest - posttest design. The samples used in the experiment is 46 students at Bachelor of Arts in Information Studies, Faculty of Humanities, Srinakharinwirot University, Thailand, selected by using purposive sampling method. The instruments used in this study were using application supports learning on computer programming in information work class, efficiency analytic of an application, learning achievement test and satisfaction questionnaires. The satisfaction used in the analysis were percentage, mean, standard deviation and t-test assisted by SPSS and descriptive statistics. The results of the study showed that the Application in design side was in the highest level of the quality with mean (x̅) of 4.68 and standard deviation (S.D.) of 0.15. The student has the posttest score significantly higher than the pretest score (p <.001). This study investigates the effectiveness of AR application learning materials and using KWL in terms of learning performance, motivation, attitude, and behavior towards different methods of learning. Our activity results favor AR application learning techniques where students’ learning motivation and performance are enhanced compared to the non- AR application learning methods. Majority of the students reported higher satisfaction on learning though application. Suggestions and comments from students revealed that using Application, students will be able to independently learn and self-test their learning at their own convenience. Instructors can use the application to provide additional study aids for the students. The Application, which is being developed as a pilot project, will be expanded, and applied as a learning tool for education.